Refusal and Politeness Strategies of Malay Speakers of English As A Second Language - Norma Saad; Siti Jamilah Bidin; Ahmad Affendi Shabdin (Universitas Muhammadiyah Sidoarjo, 2019)
Politeness is an essential part in human communication. It plays a pivotal role in establishing and maintaining good relationships and social harmony. It is reflected by linguistic and non-linguistic behavior through which we indicate that we take others’ feelings of how they should be treated into account. The present study investigated the application of politeness strategies through the linguistic behaviour of twelve Malay English as a second language (MSE) undergraduate students when refusing their higher status interlocutor’s scholarship offer to pursue their studies at an overseas university. Selection of participants was based on a purposive sampling and on the students’ MUET results. The study examined how these students employed politeness strategies as they struggled to find an equilibrium between defending their stance of not accepting the scholarship and at the same time maintaining civility towards a persistent university officer. Data on refusal interactions between the students and the university officer were obtained through an open role-play which were transcribed, classified into semantic refusal strategies, categorized into the types of sequence orders of the strategies and finally classified according to Brown and Levinson’s politeness strategies. The repertoire of MSE refusal strategies reveals positive politeness to be dominant followed by bald-on-record while negative politeness was employed minimally. Using a combination of these three types of politeness, the MSE refusal interactions show variation of politeness ranging from less to more polite. The study revealed that the degree of politeness depend very much on participants’ effort to adapt to the context of situation. The variation of strategies which reflect different degree of politeness generated by the study would be useful as pragmatic input. This input could be utilized by English language teachers to raise pragmatic awareness and to develop their students’ ability to use socially appropriate language for the situation they encounter.